Influenza A (H1N1) Pneumonia. Three cases in children. - Ariel Efrén Uriarte Méndez; Jesús Vila Díaz; Andrés Prieto Apesteguía; Dunia Chavez Amaro; Jorge Luis Capote; Orlando Leyro Salgado (Medisur, 2011)
It is made a report of three cases of pneumonia due to Influenza A (H1N1) with satisfactory evolution, assisted in the Intensive Care Unit of the Cienfuegos’s Pediatric Hospital Paquito González Cueto, and whose diagnosis were confirmed for the test Reaction in Chain of the Reverse "Polimerase-Transcriptase" (RCP-TR) in nasopharyngeal samples. The X-rays and the laboratory exams are shown. The films reveal alveolar multifocal infiltrates, different from the interstitial pattern that commonly appears in viral pneumonias. It was significant the trombocitopenia proved in one of the patients, a fact that has been rarely reported. This work try to contribute to the best knowledge of the disease in children.